Uji Performansi Alat Pengering Tipe Terowongan Hohenheim Aceh Dengan Aplikasi Proportional Integral Derivative Controller Untuk Kipas Outlet - Khathir, Rita; Hartuti, Sri; Hardiyanti, Ulfa (Universitas Trunojoyo Madura, 2022)
The purpose of this study was to evaluate the performance of Hohenheim Aceh type solar tunnel dryer with the application of proportional integral derivative (PID) controller for outlet fans. The instrumentations used were solar tunnel dryer type Hohenheim Aceh, HTC-meter, anemometer, pyranometer, and other supporting equipments. The results showed that during the drying process solar irradiation had fluctuated, where the average solar irradiation was 649 W/m2. The average temperature in the drying chamber is 40.6°C while the average temperature in the environment is 32.9°C. Conditions in the drying chamber were suitable for drying because the temperature inside the dryer was relatively higher than the ambient temperature. The average relative humidity (RH) in the drying chamber was 36% and the average RH in the environment was about 40%. The relationship between temperature and RH value was negative and strong indicated bu r-value of 0.7379. On the other hand, the relationship between solar irradiation and temperature was positive and also strong indicating that the energy source for this dryer was from solar irradiation with an R-square of 86.02% and r-value of 0.92747. The application of PID controller had improved the performance of Hohenheim Aceh type solar tunnel dryer by preventing the incident of unproper drying temperature. However, the airflow in the drying chamber was too low thus the further engineering design is needed to improve the drying system.